2020
DOI: 10.1111/dme.14466
|View full text |Cite
|
Sign up to set email alerts
|

Differential risk factor profile of diabetes and atherosclerosis in rural, sub‐urban and urban regions of South India: The KMCH‐Non‐communicable disease studies

Abstract: Aims South Asia has emerged rapidly as an epicentre of non‐communicable diseases (NCDs) specifically diabetes and cardiovascular diseases. The prevalence rate, risk factors and aetiology of NCDs in different socio‐demographic settings are not clearly understood. This study was performed to assess the prevalence of diabetes and atherosclerosis and their risk factors in urban, sub‐urban and rural communities of South India. Methods Three communities [Nallampatti (rural), Thadagam (sub‐urban) and Kalapatti (urban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In India, a major share of the older population is living in rural part of country 30 . It is evident that prevalence of different non-communicable diseases (NCDs) and risk factors for NCDs such as diabetics, hypertension, and obesity is higher in urban India 31 , 32 . Similarly, the gradual modernization and shift toward urbanized lifestyle further has triggered the lifestyle related diseases 33 .…”
Section: Introductionmentioning
confidence: 99%
“…In India, a major share of the older population is living in rural part of country 30 . It is evident that prevalence of different non-communicable diseases (NCDs) and risk factors for NCDs such as diabetics, hypertension, and obesity is higher in urban India 31 , 32 . Similarly, the gradual modernization and shift toward urbanized lifestyle further has triggered the lifestyle related diseases 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Contrasting theories have been reported that explain the prevalence disparities in urban and rural areas. Existing literature corroborates a higher prevalence of diabetes in the urban populations compared to their rural counterparts and attributes this difference to a more sedentary lifestyle in the former, worsened by access to high-calorie, processed foods and increased stress in urban settings [ 10 ]. These factors exacerbate the risk of obesity and type 2 diabetes.…”
Section: Introductionmentioning
confidence: 94%